Rural-Urban Water Sharing: Emerging conflicts and Livelihood Implications for Local Communities in Medak District. - Reddy, B. Suresh (2009)
Water transfer from agriculture to other sectors profoundly impacts upon rural livelihoods. The present paper highlights the issues arising out of rural-urban water sharing. Field research was done in six villages of Deccan area of Medak district to assess the implications of water transfer from irrigation sector to drinking water needs of Hyderabad residents. Inordinate delay in implementation of government order since 1980 has severely affected the rural economy and led to migration. The perceptions and experiences of people who shared their valuable lands for laying out drinking water pipeline to Hyderabad and still face severe drinking water shortage are also discussed. The ongoing new irrigation project under JALAYAGNAM presents a hope for migrants and agricultural labour. The study emphasizes the need for having a sustainable alternate drinking water sources for Hyderabad and concludes that rural farmers have to be given their rightful share in water from the projects of their region